VERY LOW CALORIE DIETS AFFECT LONG TERM WEIGHT LOSS AND HEALTH OUTCOMES: A SYSTEMATIC REVIEW - Putri, Sheila Amara; Arini, Shintia Yunita; Atmaka, S.Gz, MPH, Dominikus Raditya; Kusuma, Ardyanisa Raihan; Rahmawati, Anisah Firdaus; Wijanarko, Mutiara Arsya; Norfezah Md Nor; Mohd Shahid, Nadiatul Syima (Universitas Airlangga, 2025)
Introduction: In Indonesia, obesity numbers increased from 10.5% in 2007 to 14.8% in 2013 and 21.8% in 2018. Very low calorie diets (VLCD) are currently gaining popularity to reduce weight, but can lead to inadequate nutrition and potentially negative health consequences. This meta-analysis aims to evaluate VLCD effect on weight loss and overall health outcomes. Method: Data were sourced from research journal articles in databases like Crossref, PubMed, Google Scholar, and ScienceDirect, published within the last 10 years either Indonesian or English language. Only studies involving adult subjects with minimum overweight nutrition status (BMI > 23 kg/m2) were included. Result: Ten from 1063 studies qualified the selection criteria. VLCD success in weight loss depends on treatment type, duration, physical activity, and genetics. Longer and fewer-calorie VLCDs lead to more significant weight reduction, but maintaining long-term success requires a structured weight management program. VLCD benefits include improved insulin sensitivity, reduced fat, and better heart function, but it may have temporary negative effects on metabolism, aortic elasticity, constipation, sensitivity to cold, headache, and dizziness. Conclusion: VLCDs can be an effective approach in achieving significant weight reduction and positive health outcomes, especially if combined with long-term weight maintenance programs and appropriate follow-up treatment. However, the decision to undergo VLCD should be made with wisely considering individual health conditions and in consultation with dietitian or health professionals, as there are potential side effects and factors that may influence long-term success.